Kalibrering av ljussensor för Parans solpanel - Svedberg, Pär; Åkergren, Oskar (My University, 2015)
Parans Solar Lighting, a company based in Göteborg, have developed a solar panel used to bring sunlight indoors, by focusing light into optical fibres. A photosensor is used to adjust the panel’s direction, in order to maximize its intake of light, and the necessary calibration of the photosensor was previously performed manually. This degree project report describes the development of an automatic procedure for the calibration of the photosensor, and focuses on two main problems. The first problem was the development of an algorithm that performs the calibration, using values of measured luminosity, and the second problem was to find a communication solution to transfer these values from the illuminated room to the panel. The project resulted in a calibration software application and two suggestions of solutions regarding the communication, where the solar panels fibre cables are used as communication medium.
Keywords: Data- och informationsvetenskap; Computer and Information Science